Sistem Informasi Administrasi Merchandise pada Perusahaan Tour and Travel X - Hennyta Sutanto; Yulia Yulia; Leo Willyanto Santoso (Jurnal Infra, 2019)
Inventory data which has been stored so far is still manual and has not been used to generate information. Inventory data is prone to error as result for manual process. General Affair division needs a software to control inventory flow in a structured manner and generate information from the data. The software is expected to help company to control inventory flow.Before starting the application development, analysis and design of the company’s stock and the needs of General Affair were done. The analysis and design stage produce a number of diagrams that will be used to create the application.The final result of the development is an Administrative Information System. The application includes purchase, sales, delivery and receive order, inventory, customizable pivot table of purchase, sales, and inventory, income statement, purchase forecast, and merchandise, vendor, user maintenance features. Based on the research, it concluded that 75% of application features are good.